PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN - Miftahul Husnah; Nurfarida Deliani; Juliana Batubara (LPPM IAD Probolinggo, 2026)
Learning Islamic Religious Education (PAI) at the elementary school level often faces obstacles that stem not only from the curriculum or teaching methodology, but also from the psychological characteristics of children's development that have not been fully considered by educators. This study aims to identify and analyze the problems of PAI learning for elementary school-aged children from the perspective of educational psychology, including cognitive, affective, social-emotional aspects, as well as family environmental factors and teacher teaching methods. The study used a descriptive qualitative approach with a case study strategy, involving 48 informants consisting of PAI teachers, parents, students, and school principals, through in-depth interviews, participatory observation, and guided group discussions. Data were analyzed using the Miles and Huberman interactive model with source triangulation. The results of the study indicate that the dominant problem lies in the gap between the abstract nature of PAI material and the cognitive development stage of children who are still in the concrete operational phase, exacerbated by lecture and memorization methods that lack variation, thus reducing intrinsic motivation. A pattern of declining affective interest, inversely proportional to increasing cognitive abilities, was also found as children age, indicating a dissonance between pedagogical approaches and children's psychological needs at each developmental stage. This research contributes by offering a five-dimensional analytical framework (cognitive, affective, socio-emotional, family, and teacher methods) that can be used to map the problems of Islamic Religious Education (PAI) learning more precisely and contextually. The implication is that a reorientation of Islamic Religious Education (PAI) learning methods is needed based on children's psychological stages, rather than simply the transfer of religious doctrine.